(untitled) (Research, Society and Development, 2022)
Visceral leishmaniasis is a serious zoonosis, and its molecular diagnosis is an important strategy. The detection of Leishmania spp. DNA from biological samples fixed in cards could solve problems related to the collect and transport of biological samples. The purpose of this study was to detect Leishmania spp. by PCR, using canine serum fixed in cards (CSFC). For evaluation, the PCR with DNA extracted from CSFC (PCR/card) was compared to the PCR with DNA from the same serum extracted using the Qiagen kit (PCR/Qiagen) and the immunochromatography test (Rapid test - RT). The results showed that out of the 112 analyzed samples, 12 (10.71%) were positive in the PCR/Qiagen, and of those, only two failed to amplify with DNA extracted from the CSFC. The RT was positive in 11 (9.8%) samples; however, only 3 (2.75%) samples of the total agreed with the detection of Leishmania spp. through PCR. Considering the PCR/Qiagen test as the reference standard for DNA detection, the agreement with the PCR/card was nearly perfect (K = 0.8). The concentration and purity of DNA in the two extractions were not significantly different. The use of PCR with DNA from CSFC showed that it can be an interesting alternative for the diagnosis of leishmaniasis.